2002
DOI: 10.1291/hypres.25.779
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Angiotensin Type 1 and 2 Receptors on Nitric Oxide Release under Pressure.

Abstract: This study was designed to test the hypothesis that increased pressure itself could cause endothelial dysfunction and lead to decreased nitric oxide (NO) release, partly through effects on the tissue renin angiotensin system in hypertension. Cultured endothelial cells (ECs) isolated from the aortas of WKY rats were continuously exposed to a pressure of 150 mmHg in a CO2 incubator for 72 h using a pressure system, and the NOx (NO2 and NO3) and angiotensin II (Ang II) concentrations in the supernatant were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Indeed, it has been shown that mitotic ECs along the aorta are found almost exclusively at the base of arterial branches, indicating that endothelial proliferation is particularly high around bifurcations (32). It is noteworthy that hypertension, a well-recognized risk factor of aneurysm development, is believed to reduce the bioavailability of NO (12,23), and we find that NO is necessary for the WSS-stimulated proliferation. Reduced NO bioavailability could disrupt the protective responses in ECs elicited by high WSS, rendering regions such as apices of bifurcations and sharp curvatures more susceptible to mechanical damage when subjected to sustained hemodynamic stress.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, it has been shown that mitotic ECs along the aorta are found almost exclusively at the base of arterial branches, indicating that endothelial proliferation is particularly high around bifurcations (32). It is noteworthy that hypertension, a well-recognized risk factor of aneurysm development, is believed to reduce the bioavailability of NO (12,23), and we find that NO is necessary for the WSS-stimulated proliferation. Reduced NO bioavailability could disrupt the protective responses in ECs elicited by high WSS, rendering regions such as apices of bifurcations and sharp curvatures more susceptible to mechanical damage when subjected to sustained hemodynamic stress.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have shown that the production of NO or up-regulation of endothelial NOS (eNOS) activity plays a role in preventing cardiac abnormalities, such as ischemic injury and cardiac hypertrophy (5,27). In the present study, the inhibition of NOS by treatment with L-NAME completely blocked the cardioprotection of BK.…”
Section: Fig 8 Morphologic Changes Of Rat Coronary Vessels Sectionsupporting
confidence: 54%
“…A similar increase was noted in the rat (NRK-52 E) cells when subjected to pressures of (60 and 120 mmHg) for 60 and 120 min. In contrast, rat endothelial cells pressurized for 72 h at 150 mmHg had decreased NO levels, increased ANG II, and expression of ANG II receptor 2 (ATR2) (14). ANG II acting via ATR2 is believed to suppress NO in these pressurized endothelial cells.…”
Section: Discussionmentioning
confidence: 96%
“…Mechanotransduction of the signal mediates the effects of pressure on NOS (7,14,26,32). Increased amounts of NO are released by articular cartilage, periodontal ligament fibroblasts, and trabecular cells, when stimulated by static and intermittent pressure (7,26,32).…”
mentioning
confidence: 99%